SOLAR CELL SYSTEM POWER MANAGEMENT IN TRASH SKIMMER - Silvani Mulyasari, Wulan
Based on QS Ar-rum/30: 41 we can classify natural damage into two broad categories, namely land and sea. Damage to nature that is on land is easier to notice and observe because it is where most humans carry out almost 90% of their daily lives. In terms of plastic, 8.3 million tonnes are dumped into the ocean every year. Of these, 236,000 are digestible microplastics that sea creatures mistake for food. A prototype of technology to clean up garbage in calm waters has been made before at ITB. The prototype applies the basic concepts of Archimides' law regarding the floating concept, but has several obstacles and improvements to improve the performance of the prototype tool. One of them is the use of a prototype energy source in the form of solar panels and the calculation of the load that must be adjusted to the less precise motor power. The effect of angle in solar cell storage is taken into account in order to achieve maximum lighting and charging. Therefore, this paper contains research on the power management of solar cell systems in trash skimmers. This research concludes that the electric trash skimmer design is divided into several parts, namely the data transfer system, propeller motion system, conveyor motion system, and solar cells. All of these systems are then integrated into a complete circuit. The trash skimmer uses one 300 WP solar panel as a power source which can operate the trash skimmer for 80 minutes. The maximum power required by the trash skimmer is 1166 Watt and the power that can be produced by the solar panel is 1200 Watt. Power usage will be monitored using the Grafana Dashboard API and will provide an alert if the percentage of remaining power is 20%.